Concomitant occurrence of pyrrolizidine and quinolizidine alkaloids in the hemiparasite Osyris alba L. (Santalaceae) - Woldemichael, Girma Moges; Wink, Michael (Biochemical systematics and ecology, 2002)
The investigation of the alkaloid extracts of the hemiparasitic plant Osyris alba, collected from three different localities in southern France, revealed the concomitant presence of both pyrrolizidine (PA) and quinolizidine (QA) alkaloids in the samples from two of these localities. The sample from the third locality contained only PAs. The eight QAs identified were sparteine, N-methylcytisine, cytisine, methyl-12-cytisine acetate, hydroxy-N-methylcytisine, N-acetylcytisine, lupanine, and anagyrine. Of the eleven detected PAs, eight were identified as chysin A, chysin B, 1-carboxypyrrolizidine-7-olide, senecionine, integerrimine, retrorsine, senecivernine and a new alkaloid janfestine (7R-hydroxychysin A or 1R-carbomethoxy-7R-hydroxypyrrolizidine). PAs were mainly present as their N-oxides This is, to our knowledge, the first report demonstrating the simultaneous presence of two classes of alkaloids, quinolizidine and pyrrolizidine alkaloids, in a single parasitic plant. As these alkaloids do not occur in the same host plant, the results indicate that Osyris must have tapped more than one host plant concomitantly. Since both quinolizidine and pyrrolizidine alkaloids serve as defence compounds against herbivores, affecting different molecular targets, the simultaneous acquisition of the two types of alkaloids by a single plant could provide a novel mode of defence of hemiparasites against herbivores.